2019
DOI: 10.1111/jpc.14699
|View full text |Cite
|
Sign up to set email alerts
|

Cause‐specific neonatal morbidity and mortality in the Solomon Islands: An assessment of data from four hospitals over a three‐year period

Abstract: Aim: Data on stillbirths and neonatal morbidity and mortality in low-middle income Pacific Island Nations such as Solomon Islands is limited, partly due to weak health information systems. We describe the perinatal mortality and clinical factors associated with poor newborn outcomes at four hospitals in Solomon Islands. Methods: This was a registry based retrospective cohort study at three provincial hospitals and the National Referral Hospital (NRH) from 2014-2016 inclusive. Results: 23 966 labour ward births… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Stillbirth was defined in 36 data sources using 9 discrete definitions, all in completed weeks. 23-25,29,30,36,37,44,52-78 Of these, 13 were defined by gestational age in weeks and birth weight in grams, 25,29,30,44,52-55,60,61,73,75,78 and 2 specified (Australia and New Zealand) that the birth weight definition should only be used when the gestational age in weeks was not known. 52,55 Birth weight alone was not used by any country.…”
Section: Resultsmentioning
confidence: 99%
“…Stillbirth was defined in 36 data sources using 9 discrete definitions, all in completed weeks. 23-25,29,30,36,37,44,52-78 Of these, 13 were defined by gestational age in weeks and birth weight in grams, 25,29,30,44,52-55,60,61,73,75,78 and 2 specified (Australia and New Zealand) that the birth weight definition should only be used when the gestational age in weeks was not known. 52,55 Birth weight alone was not used by any country.…”
Section: Resultsmentioning
confidence: 99%
“…Other local hospital-based studies reported prevalence of 12.5% and 23.3%. 32,33 These high-prevalence rates can be explained by the increased referrals of high-risk pregnancies from rural health facilities with elevated LBW risk and may not reflect the actual LBW prevalence for the Solomon Islands’ population.…”
Section: Discussionmentioning
confidence: 99%
“…Research from Papua New Guinea and the Solomon Islands 37 , 38 , 39 , 40 highlights factors leading to poor maternal and perinatal outcomes, including stillbirth and early neonatal death. In Papua New Guinea, stillbirth is defined as a baby born without a heartbeat after 22 weeks gestation and weighing more than 500 g. 41 A recent study conducted in two provinces in Papua New Guinea identified a stillbirth rate of 23.4 per 1000 total births 37 and an early neonatal mortality rate (NMR-death within the first seven days) of 14 per 1000 livebirths.…”
Section: Maternal and Newborn Health Indicatorsmentioning
confidence: 99%